2020
DOI: 10.3892/etm.2020.8778
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‑22 is elevated in the atrium and plasma of patients with atrial fibrillation and increases collagen synthesis in transforming growth factor‑β1‑treated cardiac fibroblasts via the JNK pathway

Abstract: Our previous studies demonstrated that interleukin (IL)-22 is involved in cardiovascular diseases such as hypertension, cardiac fibrosis and aortic dissection. The purpose of the present study was to detect IL-22 expression in patients with atrial fibrillation (AF). Atrial tissue was collected from donors with sinus rhythm and patients with permanent AF, and the expression level of IL-22 and its receptors (IL-22R1 and IL-10R2) in both the left atrium (LA) and right atrium (RA) of each sample was detected. Bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…Presumably, ECH protected against HF also via regulating NF‐kappa B, FOXO1 and Akt/ERK signalling pathways. In the present study, we found that ECH down‐regulated phosphorylation levels of SAPK/JNK, the activation of JNK mediated cardiac hypertrophy, apoptosis, interstitial fibrosis, remodelling and dysfunction and inhibited the activation of JNK can protect against cardiac remodelling 30–34 . So, JNK inhibition was involved in the mechanism of ECH actions.…”
Section: Discussionsupporting
confidence: 49%
“…Presumably, ECH protected against HF also via regulating NF‐kappa B, FOXO1 and Akt/ERK signalling pathways. In the present study, we found that ECH down‐regulated phosphorylation levels of SAPK/JNK, the activation of JNK mediated cardiac hypertrophy, apoptosis, interstitial fibrosis, remodelling and dysfunction and inhibited the activation of JNK can protect against cardiac remodelling 30–34 . So, JNK inhibition was involved in the mechanism of ECH actions.…”
Section: Discussionsupporting
confidence: 49%